2014
DOI: 10.1590/2176-9451.19.1.123-137.sar
|View full text |Cite
|
Sign up to set email alerts
|

Life-quality of orthognathic surgery patients: The search for an integral diagnosis

Abstract: The decision on whether starting an orthosurgical treatment depends on the negative esthetic, functional and social impact the dentofacial deformity has on the quality of life of each patient. The objective of this article is to demonstrate the importance of assessing the quality of life of these individuals by means of applying specific questionnaires before treatment onset in order to increase the success rate of orthosurgical treatment. These questionnaires assess not only the esthetic factor, but also the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 42 publications
(74 reference statements)
1
29
0
6
Order By: Relevance
“…We also observed that specific instruments of quality of life assessment had a better association with each other than generic instruments, which, according to the author, could reinforce the greater discriminatory power of specific instruments 29 . Conversely, changes in the quality of life of patients with DDF using the OHIP-14 and OQLQ protocols were reported by a study 25 , and there were no significant differences between the scores of both protocols. However, the authors recommended OQLQ for orthopedic patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We also observed that specific instruments of quality of life assessment had a better association with each other than generic instruments, which, according to the author, could reinforce the greater discriminatory power of specific instruments 29 . Conversely, changes in the quality of life of patients with DDF using the OHIP-14 and OQLQ protocols were reported by a study 25 , and there were no significant differences between the scores of both protocols. However, the authors recommended OQLQ for orthopedic patients.…”
Section: Discussionmentioning
confidence: 90%
“…The protocols OHIP-14 and OQLQ were used to evaluate the QoL of patients undergoing orthognathic surgery, and it was concluded that it is important to evaluate aspects related to the QoL of these patients for the success of the treatment 25 .…”
Section: Introductionmentioning
confidence: 99%
“…This increase can be observed in aspects such as facial aesthetics, oral function and social interaction, the latter being the most relevant. 4,7,8 However, studies suggest that in some cases patients may overestimate postsurgical results. A new facial appearance could give patients unrealistic expectations regarding the goals of the treatment, such as success in professional or marital relationships.…”
Section: Introductionmentioning
confidence: 99%
“…A new facial appearance could give patients unrealistic expectations regarding the goals of the treatment, such as success in professional or marital relationships. 7 Evaluation of patients' QoL before and after orthognathic surgery can provide complementary data to the objective assessments of success provided by the health team.…”
Section: Introductionmentioning
confidence: 99%
“…Odzyskanie właściwych proporcji twarzy, a co za tym idzie, jej estetyki, łączy ze sobą aspekt fizjologiczny i psychologiczny [2,[5][6][7][8][9]. Ocena wyniku leczenia w dużej mierze zależy od nastawienia pacjenta oraz sposobu postrzegania swojej wady [3,10].…”
unclassified